MODEL OF IMPLEMENTATION OF THE PROGRAM OF UNIVERSAL SWIMMING TEACHING, ACCORDING TO INDICATORS OF SWIMMING POOLS PROVISION AND THE NUMBER OF CHILDREN OF PRIMARY SCHOOL AGE IN THE RUSSIAN FEDERATION - Myakonkov, V.B.; Mustafina, D.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a model for the implementation of a program for universal swimming education, taking into account the indicators of the availability of swimming pools and the number of children of primary school age in the Russian Federation. Methods and structure of the study. To achieve the goal of this study, a modeling method was used to calculate the number of participants in the interdepartmental program for teaching swimming in the framework of the lessons "Physical Education" with children of primary school age. Results and conclusions. Approbation of the model for the implementation of the program of universal swimming training was carried out on the example of the Ivanovo region. It has been established that the maximum number of participants in the interdepartmental program in this region is 63% of the average number of children of primary school age. The results of the study allow scaling this model to the entire territory of the Russian Federation in order to effectively manage and monitor the interdepartmental program of universal swimming education.